BFGF overexpression adipose derived mesenchymal stem cells improved the survival of pulmonary arterial endothelial cells via PI3k/Akt signaling pathway. (August 2019) - Wang, Pengbo; Li, Jun; Zhang, Caixin; Luo, Lin; Ni, Songshi; Tang, Zhiyuan
Abstract: Pulmonary arterial hypertension (PAH) is characterized as pulmonary arterial endothelial dysfunction and endothelial cells over proliferation, therefore, the repair of pulmonary arterial endothelial cells has been a common goal in treating PAH. In the present study, human adipose derived mesenchymal stem cells (ASCs) were transfected with bFGF lentiviral vector and co-cultured with monocrotaline pyrrole treated human pulmonary arterial endothelial cells (HPAECs). The results showed that bFGF-ASCs improved the proliferation, viability and decreased the apoptosis of HPAECs, besides, improved PAH was observed in PAH rat models. Western blot analysis showed that the PI3k and p-Akt protein expression level increased in HPAECs, suggesting the activation of the PI3k/Akt signaling pathway. With the administration of LY294002, the bFGF induced HPAECs survival and PI3k/Akt signaling activation were successfully blocked. The present study demonstrated that bFGF transfected ASCs improved the survival of HPAECs by activating the PI3k/Akt pathway.